Design and Validation of a Scale to Measure Fear of the Aquatic Environment in children - Juan Antonio Murcia; Elisa Huéscar Hernández; Luciane de Paula Borges; Neus Gómez Vera (Desafio Singular, 2020)
Although fear in early childhood is an emotion that permits survival of danger, fear of water can block and limit children's adaptive development towards this very fear. Aquatic competence is an important milestone in the improvement of general health in childhood, but there are no scales that measure how fear of water can hinder a child's development in the aquatic environment. This study aimed to design and analyze the validity of a Scale to Measure Fear of the Aquatic Environment (SFAE) to evaluate the perceived fear of the aquatic environment in three- to six-year-old children. Construct validity was also evaluated by verifying its relation to aquatic competence. The exploratory and confirmatory factor analyses support the use of five dimensions of influence on the perception of fear of the aquatic environment: social context, equipment/installations, attitude, experiences, and competence. The correlation pattern also supports construct validity showing negative and significant relations between fear and aquatic competence. The SFAE shows a promising initial validity for its use in the aquatic environment during early childhood.